2017
DOI: 10.1016/j.jhazmat.2016.09.062
|View full text |Cite
|
Sign up to set email alerts
|

Efficient degradation of sulfamethoxazole by the Fe(II)/HSO5− process enhanced by hydroxylamine: Efficiency and mechanism

Abstract: Fenton or Fenton-like processes have been regarded as feasible methods to degrade a wide variety of contaminants by generating reactive species, but the efficiency is highly affected by the slow transformation from Fe(III) to Fe(II) as well as pH. This study proposed a method by adding hydroxylamine (HA) to the Fe(II)/HSO5 -(Fe(II)/PMS) process to accelerate the degradation of contaminants, selecting a broad-spectrum sulfonamide antibiotic -

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
25
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(31 citation statements)
references
References 57 publications
5
25
0
1
Order By: Relevance
“…They also found that the detected sensitivity of p-HBA is higher than other isomers, and that it can be used for the calculation of HO ● generation with the conversion factor of 5.87 ± 0.18. This method has been employed to quantify HO ● generated in Fenton systems [22,31] and other advanced oxidation processes (AOPs) [16,3235]. However, it should be noted that HO ● radicals will react with not only BA, but also other substances such as iron ions, residual H 2 O 2 , HO ● radicals.…”
Section: Introductionmentioning
confidence: 99%
“…They also found that the detected sensitivity of p-HBA is higher than other isomers, and that it can be used for the calculation of HO ● generation with the conversion factor of 5.87 ± 0.18. This method has been employed to quantify HO ● generated in Fenton systems [22,31] and other advanced oxidation processes (AOPs) [16,3235]. However, it should be noted that HO ● radicals will react with not only BA, but also other substances such as iron ions, residual H 2 O 2 , HO ● radicals.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the MoS 2 /PMS and Fe 2+ /PMS systems achieved PNT removal of 32.9% and 23.1%, respectively, showing that both Fe 2+ and MoS 2 could effectively activate PMS to produce SO 4 ˙ − and/or ˙OH, which account for PNT degradation ( eqn (1)–(3) ). 12,19 During the Fe 2+ /PMS process, the PNT degradation slows suddenly after a period of reaction due to the fast consumption of Fe 2+ and poor reduction of Fe 3+ to Fe 2+ . 11 Notably, the obvious enhancement of PNT degradation was observed by adding MoS 2 to the Fe 2+ /PMS system, which resulted in a removal rate of 94.3% within 15 min, demonstrating the promoting effect of MoS 2 in the Fe 2+ /PMS system.…”
Section: Resultsmentioning
confidence: 99%
“… 11 Thus, the usage efficiency of Fe 2+ in the Fe 2+ /PMS system is not sufficient. 12 To facilitate the transformation of Fe 3+ to Fe 2+ , many methods have been extensively studied in recent years. For example, to maintain a proper amount of Fe 2+ in the Fe 2+ /PMS system, zero-valent iron (ZVI) was always selected as an alternative to Fe 2+ because it could generate Fe 2+ more slowly by corrosion and then reduce Fe 3+ to Fe 2+ on the ZVI surface.…”
Section: Introductionmentioning
confidence: 99%
“…Complete removal of SMX was obtained using a biochar-supported TiO 2 photocatalyst (Kim and Kan 2016). In a recent study, the maximum removal efficiency of SMX occurred at pH 3 by hydroxylamine/Fe(II)/HSO 5 − process (Liu et al 2017).…”
Section: Introductionmentioning
confidence: 99%